2011
DOI: 10.4103/0974-8237.85308
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological profile of indirect neural decompression using cage or auto graft as interbody construct in posterior lumbar interbody fusion in spondylolisthesis: Which is better?

Abstract: Study design:A prospective clinical study of posterior lumbar interbody fusion in grade I and II degenerative spondylolisthesis was conducted between Mar 2007 and Aug 2008.Purpose:The objective was to assess the clinicoradiological profile of structural v/s nonstructural graft on intervertebral disc height and its consequences on the low back pain (LBP) assessed by Visual analog score (VAS) score and oswestry disability index (ODI) . This study involved 28 patients.Inclusion criteria:Age of 30–70 years, sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The role of a cage or intervertebral spacer in PLIF surgery is to prevent foraminal stenosis [23] by maintaining intervertebral stability at the initial stage of insertion [24], facilitating intervertebral fusion, and maintaining disc height [24,25]. In the present study, the authors aimed to compare the efficacy and safety of CaO-SiO 2-P2O5-B2O3 glass ceramics spacer, including radiological and clinical results, with those of the titanium cage when inserted between L1 and S1 in patients with lumbar degenerative disease who required onelevel PLIF.…”
Section: Discussionmentioning
confidence: 99%
“…The role of a cage or intervertebral spacer in PLIF surgery is to prevent foraminal stenosis [23] by maintaining intervertebral stability at the initial stage of insertion [24], facilitating intervertebral fusion, and maintaining disc height [24,25]. In the present study, the authors aimed to compare the efficacy and safety of CaO-SiO 2-P2O5-B2O3 glass ceramics spacer, including radiological and clinical results, with those of the titanium cage when inserted between L1 and S1 in patients with lumbar degenerative disease who required onelevel PLIF.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributable to the lordotic angles of cages where cage shapes make incomplete contact with the vertebral endplate due to an anatomically concave structure. Since the original segmental lordotic angle of lumbar spine is over 10° [ 18 , 19 ], all cages with angles of 4° and 8° are not sufficient to have a significant impact in anatomical lordotic angles [ 20 ]. Similar to the results of some studies, different cage designs such as horizontal cylinder type and open box type do not influence sagittal alignment during the PLIF [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cage can be easily sterilized and stored, which greatly reduces the risk of diseases transmitted by allogeneic bone transplantation. In the case of vertebral body collapse caused by intervertebral disc degeneration, interbody fusion with cage can effectively share the load of the anterior column of the vertebral body and restore the height of the intervertebral space [21] . Although numerous analyses have con rmed that the use of cage has achieved good clinical results, cage still has many inherent shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…However, some people do not agree with this view. Abdul [21] found that the increase of intervertebral disc height and VAS score in the intervertebral fusion cage group was signi cantly better than that in the local bone graft group in the treatment of lumbar degenerative spondylolisthesis( °/ °) with PLIF operation.…”
Section: Discussionmentioning
confidence: 99%